Encoding the Record Database of Computer Based Test Exam Based on Spritz Algorithm - Zebua, Taronisokhi (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 9, No. 1 April 2018, 2018)
Computer utilization in the execution of the computer-based test is currently no strange. Almost all government agencies and companies at the time of conducting the test acceptance of new employees have been using computer-based test system online or often referred to as Computer Based Test (CBT). One of the important aspects to be considered and must be maintained in the execution of computer-based exams is the problem of question security and exam answers to abuse actions. One technique that can be done to solve the problems above is the use of cryptographic techniques. This research describes the use of spritz algorithm which is one of the cryptographic algorithms to encode the text database record of the computer-based test. The results of the encoding process can make it harder for the attackers to know the original text of the exam, so as to minimize the abuse of the exam.